Caderno de um ausente e seu outro, Menina escrevendo com pai, de João Anzanello Carrascoza - Martini, Gabriela Colombari Drun (2019)
The present research aims to analyze Caderno de um ausente (2014) and Menina escrevendo com pai (2017), both authored by the Brazilian writer João Anzanello Carrascoza. The first book brings the voice of João, who is in his fifties and, when his daughter Bia is born, writes her a kind of diary, for he believes his daughter’s life will be marked by his absence, due to his advanced age, and he would like to share some "truths" with her. Menina escrevendo com pai focuses on the voice of Bia, who, amidst her maturing process, reads her father's writings and begins a narrative from her perspective, about the years she lived with him, her writing resembling a reply to Caderno de um ausente. Our research intends to reflect on the inscription of alterity through the multiple forms of self-writing in the relationship between the self-narrator and the other-interlocutor. Carrascoza creates multiple levels of alterity ascribed to the relationship between author, narrator and reader, and to one book and another. Our work is based on Foucault’s self-writing theory, Lejeune’s studies about autobiography, Faedrich and Klinger’s autofiction, and Seligmann-Silva’s proposition about diaries. Lastly, the issue of alterity will be evaluated based on Bakhtin’s studies about the other’s voice in the discourse of the narrator and the author